2016
DOI: 10.1177/1356336x16639212
|View full text |Cite
|
Sign up to set email alerts
|

Development and optimisation of an in-service teacher training programme on motivational assessment in physical education

Abstract: Although assessment practices are commonly part of the physical education (PE) curriculum they may often frustrate rather than support students’ basic needs for autonomy, competence and relatedness. Nevertheless, assessment also provides various promising opportunities to support these basic needs and enhance learning in students. In order to address this issue, we developed an in-service teacher training programme that was grounded within contemporary theories on assessment and motivation, and aimed at improv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0
2

Year Published

2017
2017
2022
2022

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 18 publications
(14 citation statements)
references
References 46 publications
1
11
0
2
Order By: Relevance
“…Specialists say that physical education methodic, oriented on sport oriented approach to trainings' organization and fulfillment corresponds to the largest extent to the mentioned conditions [13,28,49]. Different studies show that there is noticeable positive correlation between physical culture trainings on the base of sport-oriented approach and students' psycho-physical qualities [10,43,45,47]. Increase of level of young people's professional-applied physical fitness for future professional activity [42].…”
Section: Introductionmentioning
confidence: 99%
“…Specialists say that physical education methodic, oriented on sport oriented approach to trainings' organization and fulfillment corresponds to the largest extent to the mentioned conditions [13,28,49]. Different studies show that there is noticeable positive correlation between physical culture trainings on the base of sport-oriented approach and students' psycho-physical qualities [10,43,45,47]. Increase of level of young people's professional-applied physical fitness for future professional activity [42].…”
Section: Introductionmentioning
confidence: 99%
“…A central aspect of PE that did not change with the Interest-based PE programme is that PE was delivered and assessed according to the Norwegian PE curriculum and the therein described competence aims (Utdanningsdirektoratet, 2015). However, assessment is described as a troublesome issue in PE (Leirhaug & Annerstedt, 2016;López-Pastor, Kirk, Lorente-Catalán, MacPhail, & Macdonald, 2013;Redelius & Hay, 2012;Svennberg, Meckbach, & Redelius, 2018) and a challenge to students' experiences of autonomy, competence, and relatedness in the subject (Krijgsman et al, 2017;Slingerland et al, 2016). Previous research found that students consider "having the right body and sporting ability" (Redelius & Hay, 2012, p. 218) to be a key factor in receiving high grades in PE.…”
Section: Sports Discourse and Assessment In Pementioning
confidence: 99%
“…Özyürek (1981) attributes this necessity upon the developments and advancements in science, society, schools, and teaching processes, and upon the expectations in teachers' fields of personal interest (Altınışık, 1996;Küçükahmet, 1998). In-service training provides teachers with the opportunity to acquire knowledge and skills in adapting to structural and cultural changes at schools (Nawab, 2017), to transform contemporary theories and models into educational activities, to operationalize educational reforms by ensuring coordination between theory and practice (Bush, 2007;Slingerland et al 2017), and to create changes in classroom practices, attitudes, beliefs, and learning outcomes (Guskey, 2002).…”
Section: Introductionmentioning
confidence: 99%